Trends in self-reported prevalence and management of hypertension, hypercholesterolemia and diabetes in Swiss adults, 1997-2007 - Marques-Vidal Pedro; Vollenweider Peter; Paccaud Fred; Estoppey Daniel (BMC, 2011)
Abstract Background Switzerland has a low mortality rate from cardiovascular diseases, but little is known regarding prevalence and management of cardiovascular risk factors (CV RFs: hypertension, hypercholesterolemia and diabetes) in the general population. In this study, we assessed 10-year trends in self-reported prevalence and management of cardiovascular risk factors in Switzerland. Methods data from three national health interview surveys conducted between 1997 and 2007 in representative samples of the Swiss adult population (49,261 subjects overall). Self-reported CV RFs prevalence, treatment and control levels were computed. The sample was weighted to match the sex - and age distribution, geographical location and nationality of the entire adult population of Switzerland. Results self-reported prevalence of hypertension, hypercholesterolemia and diabetes increased from 22.1%, 11.9% and 3.3% in 1997 to 24.1%, 17.4% and 4.8% in 2007, respectively. Prevalence of self-reported treatment among subjects with CV RFs also increased from 52.1%, 18.5% and 50.0% in 1997 to 60.4%, 38.8% and 53.3% in 2007 for hypertension, hypercholesterolemia and diabetes, respectively. Self-reported control levels increased from 56.4%, 52.9% and 50.0% in 1997 to 80.6%, 75.1% and 53.3% in 2007 for hypertension, hypercholesterolemia and diabetes, respectively. Finally, screening during the last 12 months increased from 84.5%, 86.5% and 87.4% in 1997 to 94.0%, 94.6% and 94.1% in 2007 for hypertension, hypercholesterolemia and diabetes, respectively. Conclusion in Switzerland, the prevalences of self-reported hypertension, hypercholesterolemia and diabetes have increased between 1997 and 2007. Management and screening have improved, but further improvements can still be achieved as over one third of subjects with reported CV RFs are not treated.